The role of key post-translational modifications in the nuclear translocation of STAT3 dimers upon cytokine stimulation - Alves, Daniela Martins (2022)
Tese de mestrado, Bioquímica (Bioquímica), Universidade de Lisboa, Faculdade de Ciências, 2022